2023
DOI: 10.9734/jeai/2023/v45i92193
|View full text |Cite
|
Sign up to set email alerts
|

Field Screening of Elite Cassava (Manihot esculenta) Mutant Lines for their Response to Mosaic and Brown Streak Viruses

Lydia Chepkoech Kimno,
Miriam Gaceri Kinyua,
Isaac Kofi Bimpong
et al.

Abstract: Cassava Brown Streak Disease (CBSD) and Cassava Mosaic Disease (CMD) have been major limiting biotic factors to the productivity of cassava farming in Kenya. Development of resistant cassava varieties is most effective way. The study was to determine response of elite cassava lines to CBSD and CMD under field conditions on different agro-ecological zones in Kenya. Screening was done under hot-spot field conditions where five lines together with their parents were evaluated in Randomized Complete Block Design w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…A non-GM approach to mutation induction has also been attempted to develop mutants with a tolerance for CMD and CBSD. Field trials conducted in different agro-ecological regions in Kenya have revealed that the three mutants have better tolerance to these diseases than their respective parents [ 56 ]. On the other hand, an attempt to increase β carotene content by co-expression of transgenes for deoxy-d-xylulose-5-phosphate synthase and bacterial phytoene synthase in cassava resulted in reduced dry matter and starch content, despite a 15–20-fold increase in carotenoids [ 57 ].…”
Section: Root and Tuber Cropsmentioning
confidence: 99%
“…A non-GM approach to mutation induction has also been attempted to develop mutants with a tolerance for CMD and CBSD. Field trials conducted in different agro-ecological regions in Kenya have revealed that the three mutants have better tolerance to these diseases than their respective parents [ 56 ]. On the other hand, an attempt to increase β carotene content by co-expression of transgenes for deoxy-d-xylulose-5-phosphate synthase and bacterial phytoene synthase in cassava resulted in reduced dry matter and starch content, despite a 15–20-fold increase in carotenoids [ 57 ].…”
Section: Root and Tuber Cropsmentioning
confidence: 99%